A Field Guide to Musicians' Tinnitus - Wartinger, Frank; Gould, Nancy; Rogel, Melissa (Seminars in Hearing, 2024)
Tinnitus onset is associated with numerous auditory and psychological correlates in the general population, and are compounded in musicians. With the assistance of patient quotes and a case study, this article explores the vocational, emotional, and practical factors which should be considered by clinicians who work with this population. To better serve music-exposed individuals, especially music industry professionals, telehealth has proven to be a viable and advantageous care delivery method due in part to decreased barriers to access.
Keywords: tinnitus; telehealth; teleaudiology; musician; psychological health